2014
DOI: 10.1186/1471-2415-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-domain optical coherence tomography evaluation of postoperative cystoid macular oedema following phacoemulsification with intraoperative complication

Abstract: BackgroundTo report the rate of cystoid macular oedema (CMO) as detected by spectral-domain optical coherence tomography (SD-OCT) after intraoperative complication during phacoemulsification. The secondary objectives include comparing mean macular thickness and best-corrected visual acuity (BCVA) between those who developed postoperative CMO against those who did not.MethodsThis is a prospective cohort study conducted in a tertiary hospital between July 2009 and June 2010. Serial SD-OCT and BCVA were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…However, some factors are diagnosed to increase the risk of macular thickening such as the presence of insulin-dependent diabetes mellitus, duration of diabetes ≥10 years, the severity of diabetic retinopathy, and prior treated diabetic ME. The results of the present study are in contrast to the ndings of Elsawy et al 20 , and Singal et al 8 . Our patients (both ketorolac and placebo groups) had good diabetes control (FBS≤126 mg/dl and HbA1c <7%), most of them had no diabetic retinopathy or mild nonproliferative diabetic retinopathy and used oral agents or just were on diet to control their diabetes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, some factors are diagnosed to increase the risk of macular thickening such as the presence of insulin-dependent diabetes mellitus, duration of diabetes ≥10 years, the severity of diabetic retinopathy, and prior treated diabetic ME. The results of the present study are in contrast to the ndings of Elsawy et al 20 , and Singal et al 8 . Our patients (both ketorolac and placebo groups) had good diabetes control (FBS≤126 mg/dl and HbA1c <7%), most of them had no diabetic retinopathy or mild nonproliferative diabetic retinopathy and used oral agents or just were on diet to control their diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…13 Ketorolac tromethamine is a potent non-steroidal anti-in ammatory drug (NSAID) that inhibits cyclooxygenase enzymes and thus decreases the level of ocular prostaglandins and consequently the chance of cystoid ME when applied topically. [15][16][17][18] In the study by Nikkhah et al, the effective and sustainable in uence of the topical ketorolac was reported in diabetic patients to treat diabetic ME, the same nding was also reported by Elsawy et al, 20 in spite of the above-mentioned studies, inconclusive therapeutic effects of topical NSAIDs to prevent post-phacoemulsi cation ME was determined by a meta-analysis conducted in tromethamine 0.5% on post-phacoemulsi cation macular thickening compared to placebo in diabetic patients.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This complication would occur in 8% of cases and can be chronic despite optimal treatment in 3% of cases. 1,2 This pseudophakic macular edema generally appears between the first and the sixth month postoperatively. The pathophysiology of pseudophakic cystoid macular edema is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated role of phacoemulsification on Central Macular Thickness (CMT). 6 Any change or oedema after cataract surgery has profound effect on vision of patient undergoing cataract surgery. Different studies have also evaluated the role of uneventful phacoemulsification cataract surgery on Subfoveal Choroidal Thickness (SFCT).…”
Section: Introductionmentioning
confidence: 99%